2007
DOI: 10.3168/jds.2007-0431
|View full text |Cite
|
Sign up to set email alerts
|

Soymilk as a Novel Milk Replacer to Stimulate Early Calf Starter Intake and Reduce Weaning Age and Costs

Abstract: The primary objective was to determine the effects of partial replacement of whole milk with soymilk on preweaning calf performance and weaning costs. Following 3 d of colostrum and transition milk feeding, 18 male and 9 female neonatal Holstein calves (41.6 +/- 1.6 kg of body weight; mean +/- SE) were assigned in a completely randomized design to 3 treatments offered at 10% of body weight (wet basis) including 1) whole milk (control), 2) 75% whole milk + 25% soymilk (S25), or 3) 50% whole milk + 50% soymilk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
1
25
0
2
Order By: Relevance
“…The presence of trypsin inhibiting factors and changes in the intestinal flow could have influenced animal's weight (Drackley et al, 2006). The absence of effect in ADG agrees with similar results obtained by Ghorbani et al (2007). In these type of milk replacers, daily gain is mostly affected by the liquid diet composition, not by the volume fed; therefore, there is no compensatory effect to justify an increase on milk replacer feeding (6 vs 8 L/d) when low quality CP is included.…”
Section: ------------------------------------------------------------supporting
confidence: 78%
“…The presence of trypsin inhibiting factors and changes in the intestinal flow could have influenced animal's weight (Drackley et al, 2006). The absence of effect in ADG agrees with similar results obtained by Ghorbani et al (2007). In these type of milk replacers, daily gain is mostly affected by the liquid diet composition, not by the volume fed; therefore, there is no compensatory effect to justify an increase on milk replacer feeding (6 vs 8 L/d) when low quality CP is included.…”
Section: ------------------------------------------------------------supporting
confidence: 78%
“…Terui et al (1996) demonstrated that wheat gluten can replace milk protein up to 50% in milk replacer without compromising the growth of calves. Ghorbani et al (2007) suggested that replacing 25% rather than 50% of whole milk with soymilk may be the optimum use of soymilk as a milk replacer during the first 2 to 3 wk of age in calves. Replacing 60% of the whey proteins in an all-milk protein milk replacer with soy protein concentrate decreased growth rates and feed efficiency and decreased villus height and crypt depth in the jejunum and villus height in the ileum of calves.…”
mentioning
confidence: 98%
“…Soybean is a source of high quality, relatively inexpensive protein that has potential for use in a milk replacer Ghorbani et al, 2007). Soy protein sources such as soy protein concentrate and soy protein isolate have partly been used in milk replacers (Silva et al, 1986;Drackley et al, 2006).…”
mentioning
confidence: 99%
“…Soya protein and wheat protein has an acceptable amino acid profile and is relatively inexpensive compared to most other alternative proteins (Vermeire, 2005). In some countries, soymilk is being used as a novel milk replacer in calf raising facilities (Ghorbani et al, 2007). Soybean meal is an excellent source of vegetable protein (Carpenter 1951).…”
Section: Introductionmentioning
confidence: 99%